Nilai Pendidikan Karakter dalam Sya’ir Tawar Sedenge - Ramadan Ramadan; Hamdan Hamdan; Novita Mahbengi (Medan Resource Center, 2026)
This study examines the character values and forms of character education embedded in Sya’ir Tawar Sedenge within the Gayo community of Central Aceh Regency. It addresses how the poem embodies moral values and how these values are transmitted through cultural practices. The research employed a descriptive qualitative method using observation, interviews, and documentation as data collection techniques. Primary data were obtained from key informants of the Majelis Adat Gayo, including the Head of the Library Division and the Deputy Head II of the Customs Division. Data were analyzed through the processes of data reduction, data display, and conclusion drawing. The findings demonstrate that Sya’ir Tawar Sedenge conveys fundamental character values, including religiosity, honesty, responsibility, and mutual cooperation, while simultaneously reinforcing cultural identity and patriotism. The study further reveals that the poem functions as a moral and cultural guideline that has been transmitted across generations and is implemented through family education, formal schooling, and traditional ceremonies. The study concludes that Sya’ir Tawar Sedenge serves not only as a medium for preserving Gayo cultural heritage but also as an effective instrument for strengthening character education and fostering social cohesion in contemporary society.